POLITIK-INSTITUSIONAL DALAM IMPLEMENTASI SISTEM PENERIMAAN NEGARA SECARA ELEKTRONIK - agung Darono (Jurnal BPPK : Badan Pendidikan dan Pelatihan Keuangan, 2015)
Institutional politics is a concept to describe how power and authority of actors within an organization fosters an intertwined situation between the parties involved so that an emerging “institusion” (i,e. Particular pattern of behavior that is stable, repetitive and purposeful) will appear or destroyed. The development implementation, acceptance, as well as endurance of” System penerimaan negara secara elektronik”(SPNsE, i,e, IT based state revenue administration system) as an institution obviously cannot be segregated from such complex interplay. Lesson learned from the implementation of the SPNsE is that an organization (government body) could take advantage of institutional and political aspects and then utilized them as adriver to achieve organizational goals. This study deployed interpretive policy anaysis as data anaysis techniques by utilizing various source of secondary data in the form of system documentation in broad sense such as legal provisions system manual operation and as well as memorandum of cooperation agreements between parties involved in the system development and implementation. This research concludes an in-depth understanding of the research problem, that is, the institutional politics aspects in the implementation of SPNsE intertwined with; (1) particular institutional control that serves as accelerators on the creation of a new institution ; (2) the organizational actors that capable of using institusional-agency to expand certain functions of the system; (3) the dominant discoursein affering agents to create, transform or eliminate an institutio; (4) some difficulties on how an institutional agency is reaching out other institutions that are beyond the power of such actors.